Islamic New Public Management Model for Excellent Service in Government Institutions - Nikmatul Masruroh; Halimatus Zahra; Nurul Widyawati Islami Rahayu; Muhammad Sami (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2026)
Introduction: The service of an institution is a measure of public satisfaction with employee performance. Therefore, innovation in service is needed to keep customers happy and coming back. In addition, public service is also crucial in government, because the public needs comfort in receiving service. This study aims to first explore the practice of excellent service in government institutions. Second, analyze the new public management model in services in government institutions. Third, analyze the Islamic values ​​contained in the new public management in services in government institutions. Fourth, create an Islamic new public management model in services in government institutions. Methods: This study uses a qualitative approach with a case study type. The case focused on in this study is the presence of one-stop service in Investment and One-Stop Integrated Services Agency in Jember Regency. The determination of research subjects was carried out purposively, with the criteria for selecting informants who were directly related to the one-stop service model. Data were collected using observation, interview and documentation techniques. Data were analyzed using the Miles and Huberman interactive model technique and tested through source triangulation.  Results: This study provides results, first, excellent service that is carried out leads to digital transformation making licensing services faster to complete, previously 1 week to 1 month, after the transformation it became only 1 day. The innovation is to make the licensing service a one-stop service. Thus, employee performance is maximized because the public does not need to move from location to location when doing licensing. Second, the new public management model that is carried out is to present the OSS (Online Single System) system in service. Third; Islamic values ​​that are present in the practice of new public management, namely the value of siddiq (honesty) which is in the form of transparency, the value of amanah (integrity) which is the commitment of employees, fathonah (smart) which is innovative and creative, the value of discipline and the value of efficiency. Fourth, the Islamic new public management model offered to maximize excellent service, namely the model of integrating Islamic values ​​in service, so that service is not only technology-based but also ethics-based. Conclusion and suggestion: The conclusion is that digital transformation in the licensing office with a one-stop model is a model for maximizing employee performance and has an impact on public satisfaction.